ConfLLVM: A Compiler for Enforcing Data Confidentiality in Low-level Code - Brahmakshatriya, Ajay; Kedia, Piyus; McKee, Derrick P.; Garg, Deepak; Lal, Akash; Rastogi, Aseem; Nameti, Hamed; Panda, Anmol; Bhatu, Pratik (EuroSys 2019, 2019)
We present a compiler-based scheme for protecting the confidentiality of sensitive data in low-level applications (e.g. those written in C) in the presence of an active adversary. In our scheme, the programmer marks sensitive data by writing lightweight annotations on the top-level definitions in the source code. The compiler then uses a combination of static dataflow analysis and runtime instrumentation to prevent data leaks even in the presence of low-level attacks. To keep the overheads of the instrumentation low, the compiler uses a novel memory layout and a taint-aware form of control flow integrity. We formalize our scheme and prove its security. We have also implemented our scheme within the LLVM compiler and evaluated it on the CPU-intensive SPEC micro-benchmarks, and on larger, real-world applications, including the NGINX webserver and the OpenLDAP directory server. We find that performance overheads introduced by our instrumentation are moderate (average 12% on SPEC), and the programmer effort to port the applications is minimal.